A multi-criteria model analysis framework for assessing integrated water-energy system transformation pathways. (15th January 2018) - Parkinson, Simon C.; Makowski, Marek; Krey, Volker; Sedraoui, Khaled; Almasoud, Abdulrahman H.; Djilali, Ned
Highlights: Integrated capacity planning model incorporating water and energy systems decision-making. Modified version of the reference point methodology applied to balance multiple design criteria. Application to the water-stressed country of Saudi Arabia. Multi-criteria tool efficiently identifies ambitious solutions across sustainability objectives. Abstract: Sustainable development objectives surrounding water and energy are interdependent, and yet the associated performance metrics are often distinct. Regional planners tasked with designing future supply systems therefore require multi-criteria analysis methods and tools to determine a suitable combination of technologies and scale of investments. Previous research focused on optimizing system development strategy with respect to a single design objective, leading to potentially negative outcomes for other important sustainability metrics. This paper addresses this limitation, and presents a flexible multi-criteria model analysis framework that is applicable to long-term energy and water supply planning at national or regional scales in an interactive setup with decision-makers. The framework incorporates a linear systems-engineering model of the coupled supply technologies and inter-provincial transmission networks. The multi-criteria analysis approach enables the specification of diverse decision-making preferences for disparate criteria, and leads to quantitative understanding of trade-offs between the resulting criteria values of the corresponding Pareto-optimal solutions. A case study of the water-stressed nation of Saudi Arabia explores preferences combining aspiration and reservation levels in terms of cost, water sustainability and electricity sector CO2 emissions. The analysis reveals a suite of trade-off solutions, in which potential integrated water-energy system configurations remain relatively ambitious from both an economic and environmental perspective. The results highlight the importance of identifying suitable tradeoffs between water and energy sustainability objectives during the formulation of coupled transformation strategies.